2009
DOI: 10.1097/cpm.0b013e31819b3a41
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Statins in Respiratory Diseases

Abstract: Statin drugs inhibit 3-hydroxy-3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Pleiotropic effects of statins have been reported in several malignancies, especially respiratory infections [ 47 , 48 ], acute lung injury [ 49 ], pulmonary hypertension [ 50 ], community-acquired pneumonia, chronic obstructive pulmonary disease [ 51 ], and interstitial lung disease [ 52 ]. Statins have shown various beneficial anti-inflammatory and immunomodulatory properties by affecting intracellular signaling pathways [ 53 , 54 ] that are independent of their lipid-lowering ability [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotropic effects of statins have been reported in several malignancies, especially respiratory infections [ 47 , 48 ], acute lung injury [ 49 ], pulmonary hypertension [ 50 ], community-acquired pneumonia, chronic obstructive pulmonary disease [ 51 ], and interstitial lung disease [ 52 ]. Statins have shown various beneficial anti-inflammatory and immunomodulatory properties by affecting intracellular signaling pathways [ 53 , 54 ] that are independent of their lipid-lowering ability [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 These observations support the hypothesis that a reduction in mortality associated with statin use might be attributable to an alternative biological pathway rather than cholesterol reduction and a reduced incidence of fatal CVD. Indeed, it is well known that statins have much wider actions than their effect on cholesterol -including anti-oxidant, anti-neoplastic (apoptotic), and immune modulating effects [11][12][13][14] -and statins reduce both pulmonary inflammation and systemic inflammation.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
“…However, laboratory-based and animal research has shown that statins have a diverse range of 'pleiotropic effects' including antiinflammatory actions, anti-thrombotic properties, anti-oxidant effects, and immunomodulatory effects. [10][11][12][13] Recent evidence suggests that statins reduce pulmonary inflammation and may suppress the inflammation associated with cigarette smoke and ameliorate the associated structural and functional abnormalities in the lung. 12,14 It is therefore possible that these effects may result in therapeutic benefits in patients with COPD over and See linked editorial by Pearson on pg 5 above reducing their risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Pleiotropic effects of statins have been reported in several malignancies, especially respiratory infections [43,44], acute lung injury [45], pulmonary hypertension [46], community-acquired pneumonia, chronic obstructive pulmonary disease [47], and interstitial lung disease [48]. Statins have shown various bene cial anti-in ammatory and immunomodulatory properties by affecting intracellular signaling pathways [49,50] that are independent of their lipid-lowering ability [51].…”
Section: Discussionmentioning
confidence: 99%